Glomangiomyoma of the clitoris: A case report and literature review - Huan Xie; Sameera Ansar; Lyndal Anderson; Samir Saidi; Yu Xuan Kitzing; Sunaina Anand (Elsevier, 2021)
Glomus tumor is an uncommon, benign, soft-tissue lesion in which the cells recapitulate the structure of the normal modified smooth muscle cells of the glomus body. Glomus tumors usually occur in tissues that normally contain glomus bodies; only rarely can they develop in sites where glomus bodies are normally sparse or absent. There are three subtypes of glomus tumor, with glomangiomyoma being the rarest. No more than 10 cases of glomus tumor in female genitalia have previously been reported, involving the vulva, vaginal area, periurethral area and clitoris. A clitoral glomangiomyoma is extremely rare. This is a case report of a glomangiomyoma in the clitoral area. Published reports of glomus tumor in the female external genitalia are reviewed.